The International Vehicle Aerodynamics Conference 2014
DOI: 10.1533/9780081002452.3.81
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of vehicle ride height and wheel position influence on the aerodynamic forces of ground vehicles

Abstract: To prevent test vehicles from movement during experiments in modern aerodynamic wind tunnels, fastening struts are typically used for a rigid connection between the model and the force balance underneath the wind tunnel floor. A weakness of this experimental setup is that such struts limit the vertical movement of the vehicle. By analysing experimental data from the Volvo Cars wind tunnel and corresponding CFD simulations the differences in measurements using struts with and without vertical displacement have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 7 publications
2
3
0
3
Order By: Relevance
“…Even with the slight discrepancies described taken into account, the additional vertical displacement in most cases still lies in the range of 4 to 6 millimeters, which corresponds well with the data obtained by Vdovin [7], where the vertical displacement due to tire radial expansion for a relevant velocity of 140 kph is around 5 millimeters for both axles. It can therefore be concluded that the phenomenon in question can be held responsible for the fact that ride heights experienced by a car on the road are significantly higher than expected when only taking into account aerodynamic loading.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…Even with the slight discrepancies described taken into account, the additional vertical displacement in most cases still lies in the range of 4 to 6 millimeters, which corresponds well with the data obtained by Vdovin [7], where the vertical displacement due to tire radial expansion for a relevant velocity of 140 kph is around 5 millimeters for both axles. It can therefore be concluded that the phenomenon in question can be held responsible for the fact that ride heights experienced by a car on the road are significantly higher than expected when only taking into account aerodynamic loading.…”
Section: Resultssupporting
confidence: 88%
“…As shown, for example, by Regert [8], the aerodynamic drag of a vehicle decreases as the wheel diameter in a wheel housing of constant shape increases. This was also confirmed by Vdovin [7], who stated that with the vertical position of the body fixed, increasing velocities, i.e. increasing wheel diameter, cause the drag of the vehicle to decrease compared to the case where vertical displacement is allowed.…”
Section: Shrnutísupporting
confidence: 55%
See 3 more Smart Citations